Análise funcional clínica e o processo de mudança - Törneke, Niklas (Perspectivas em Análise do Comportamento, 2021)
The term functional analysis has an extremely central position within behavior analysis, ever since it was first coined by Skinner. Its use within the clinical part of applied behavior analysis, or what is often called psychotherapy, is still somewhat controversial. This article claims that the term and the phenomena it describes should hold a central position also in psychotherapy. But for that to happen an analysis of human language must be included and relational frame theory (RFT) offers that kind of analysis. The article applies the conclusions from such an analysis to the clinical dialogue and gives practical directions on how a clinical functional analysis can be conducted within that context.